The study of arterial and venous Doppler in high risk pregnancies and its role in perinatal outcome - Tabitha, S.; Rajini, Madishetti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Antepartum foetal surveillance is the corner stone in the management of high risk pregnancies, aimed at reducing maternal and perinatal mortality and morbidity. This study was conducted to analyse the blood flow in umbilical artery, middle cerebral artery, umbilical vein and ductus venous using doppler ultrasound in high risk pregnancies. Methods: This was a prospective study conducted in pregnant patients with high risk factors after 28 weeks of gestation who got admitted in the Department of Obstetrics and Gynaecology at Care Hospital, Hyderabad during the period from October 2013 to December 2014. Results: Patients were divided into two groups, first with normal Doppler and second with abnormal Doppler, containing 76 and 20 patients respectively. Group 2 is again 4 sub-groups according to the vessel affected. Group A included the cases with affected umbilical artery, Group B included the cases with affected middle cerebral artery, Group C included the cases with both affected umbilical artery and middle cerebral artery (UA+MCA), Group D included the Cases with the affected umbilical artery, middle cerebral artery and Ductus Venosus (UA+MCA+DV) containing 12, 2, 4 and 2 patients respectively. There were more number of emergency caesarean sections than vaginal deliveries which is statistically significant (p <0.034), there were more number of sick babies than healthy babies and there are more number of still births which is statistically significant (p <0.0001), there are more number of low birth weight babies in comparison to normal weight, which is statistically significant (p <0.0037). Distribution of cases with abnormal Doppler depending on vessel abnormality according to gestational age at the time of delivery, mode of delivery, perinatal outcome, birth weight, which was statistically significant. The sensitivity and specificity of abnormal Doppler in predicting perinatal outcome is 45% with (95% CI 26.9-64.0) and 89.5% with (95% CI 79.0-95.3) respectively. The positive predictive value is 65% with (95% CI 40.9-83.6) and negative predictive value is 78.9% with (95% CI 67.7-87.1). Conclusions: This study recommends that all high risk pregnant women should undergo serial foetal monitoring. When doppler abnormalities are detected, delivery should be conducted at a tertiary care centre where facilities for caesarean section and NICU are present.